3D VISUALIZATION OF CULTURAL HERITAGE USING TERRESTRIAL LASER SCANNER (A Case Study : Monument of Heroes, Surabaya, East Java) - Pribadi , Cherie Bhekti; Handayani, Hepi Hapsari; Rachmawan, Firdiansyah Eka (Departemen Teknik Geomatika ITS, 2016)
Research subjects reported was the visualization of three-dimensional (3D) surface models in three-dimensional mapping survey using terrestrial laser scanning (TLS). Tugu Pahlawan (Heroes Monument), located in Surabaya city center near the office of the Governor of East Java was chosen as the research object.Laser technology instruments used for comparison is GeoMax Zoom 300 (Terrestrial Laser Scanner) and Gowin TKS-202 (Electronic Total Station) as well as for geodetic GPS coordinates and altitude reference measurement Heroes Monument are georeferenced. Coordinate measurement results Electronic Total Station and Terrestrial Laser Scanner are then converted into global coordinates (UTM) using georeferencing process from Geodetic GPS measurement results. Coordinates, diameter and height of Tugu Pahlawan calculated for each model. Statistical test is used as data validation terrestrial laser scanner with electronic total station.With 90% confidence interval on statistical tests, 80% of them into confidence intervals. Height of Tugu Pahlawan according to archived data is 41.448 m, in contrast with the results of measurements from Total Station is 41.144 m, while the results of TLS is 41.447 m. Statistical test results concluded that the height of heights TLS is outside the confidence interval. Expected in the future, such as the visualization of 3D surface models can be used for documentation, preservation and reconstruction of cultural heritage.